Pembuatan Sistem Informasi Manajemen Aset Berbasis Website Pada Perusahaan Elektronika X - Yohanes Christian; Yulia Yulia; Djoni Haryadi Setiabudi (Jurnal Infra, 2018)
X Company provides various kinds of electronic things and home appliances, to fulfill all sales transactions on every branches store then it is necessary to have many kinds of assets likes vehicles for delivery services, storefronts for items display and many other needs. And of course every assets need some specific types of maintenances. For now, every process of scheduling maintenances, registering maintenances and recording maintenances realization are done by written manual on paper or by direct spoke to each other’s. The current applied process will have some consequences such as forgetting some assets maintenance and difficulties in creating reports because the data is written on the paper. So it is needed to have a system that records all the broken assets reports, maintenance schedules and maintenance realization properly.To resolve this issue, a system based on Computerized Maintenance Management System(CMMS) with some adaption to the current process of the company that obtained from the direct interview will be created. The system will be made based on web based system using a programming languages such as HTML, CSS, Codeigniter Framework based on PHP, JavaScript, Ajax and using SQL Server as database.The conclusion after finished to develop the system are the scheduling process is have worked correctly but with some exclusion that allow to work overtime with PIC Aset approval and the spare part stock forecast also worked correctly for fulfill the spare parts requests but will not worked to fulfill abnormal requests.